EVALUASI ALAT PERAGA KAMPANYE PEMILIHAN UMUM DI ERA DEMOKRASI ELEKTORAL - Yuliyanto, Muchamad (JURNAL ILMU SOSIAL, 2014)
Promotions material as an outdoor media campaign by the politicians in general election needs to be evaluated . Moreover, an election is always followed by public developments such as quality increasing of public education and knowledge as voters, ease of access to information, the critical attitude in responding to society's problems almost always become the message in the campaign promotions material.This study aims to investigate the general public's response to campaigns in the era of electoral democracy that is characterized by the usage of massive outdoor media. This research is a descriptive qualitative study with in-depth interview data collecting techniques.The results showed several things: first , there is a difference of perception between voters and candidates related campaign promotions material. Voters agreed that the presence of campaign promotions material is now a day as at too many and ruining environment’s beauty. While politicians felt that the campaign promotions materialwhich have been distributed are still lacking. Second, the informants from higher education level thought that campaign promotions material sought to enhance public awareness and knowledge of the candidates if it was used correctly . But for votersfrom lower education level, campaign promotions material is not able to increase their awareness about particular candidate , especially in the legislative elections . Third , the campaign method which considered to be most able to attract voters is politician’s activity and contributions in the community.